Rotasi Opioid dan Manajemen Nyeri pada Pasien Cancer Pain Akibat Kanker Serviks Stadium 4 dan Fistula Rectovagina - Mahmud; Widyastuti, Yunita; Atmanagara, Dikho (Jurnal Komplikasi Anestesi, 2021)
Pain is an unpleasant experience that will be felt by almost all cancer patients, which can result in reduced quality of life for cancer patients. Administration of opioid analgesics by increasing the dose to achieve the expected analgesia potentially followed by harmful side effects to the patient. In this situation, it is necessary to rotate the opioid to obtain an adequate dose of analgesia without increasing the risk of using the opioid. We present a case report of severe cervical cancer pain not controlled by oral opioid administration. The patient was assessed for the degree of pain and opioid rotation to control the cancer pain. After the rotation of opioids, it was found that pain was controlled by giving the new type and route of the opioid.